ANALISIS PENGEMBANGAN DESA SIAGA AKTIF PRATAMA KE MADYA DI KECAMATAN RAHUNING KABUPATEN ASAHAN TAHUN 2019 - Dianty Elfirita Damanik; Muhammad Badiran; Asriwati Asriwati (Jurnal Mutiara Kesehatan Masyarakat, 2020)
The development of Active Alert Village is one of the strategies in realizing Healthy Indonesia. The coverage of it at Rahuning District of Asahan Regency has now reached 100%, but if it is evaluated who really has real preparedness may not have reached 50%. Active Alert Village Pratama to Madya for 3 villages namely Rahuning I Village, Perkebunan Gunung Melayu Village, and Gunung Melayu Village. This study aims to analyze the development of active alert village Pratama to Madya. This research type used qualitative research with a descriptive approach. The study was conducted at Rahuning District. The research informants were 8 people. Data analysis used Qualitative with the stages of data reduction, data display, and conclusion or verification. The results showed that team development officers routinely done activities. The development of the community team has been formed involving the community apparatus; community leaders, PKK activists, and others. The meeting was held routinely to discuss the development of Active Alert Village. The Introspective Survey was still less than optimal because there was no provisioning of skills for the Introspective Survey. Village Community Meetings (MMD) was routinely done involving community leaders, village midwives, organizations in the village such as the PKK driving team. The conclusion shows that only 2 villages can be developed into active Madya villages; Rahuning I Village and Gunung Melayu Village supported by availability of human resources, cross-sector collaboration and programs, training and cadre coaching, infrastructure or health facilities, counseling. The main limiting factor in developing active alert village pratama is that there is a lack of funds, and the new APBDes are budgeted for 2020.